On the specifics of Japan’s humanitarian cooperation with Asia-Pacific countries and Russia in 2024 - Kazakov O.I. (Восточная Азия: факты и аналитика)
Over the past five years humanitarian ties between Japan and other Asia-Pacific countries have shown a rapid forced “cooling” due to numerous local and global restrictions during the peak of the COVID-19 epidemic in 2020–2021, and a gradual recovery in the post-COVID era. Against the backdrop of the recovery of countries after the pandemic, other constraints have emerged, primarily of a military and political nature, which “freeze” the further development of humanitarian ties. Since February 24, 2022, such a constraint in Russian-Japanese relations has been Russia's special military operation, which led to a global split between supporters and opponents of Ukraine. Nevertheless, Japan strives to establish and develop relations with the Asia-Pacific countries, which resulted, in particular, in a new record of foreign tourists visiting Japan in 2024. The situation in Russian-Japanese relations has seriously worsened, due to the actual development of sanctions and information war between the two countries. However, humanitarian ties between Russia and Japan have not ceased yet.